2017
DOI: 10.1177/0363546517728717
|View full text |Cite
|
Sign up to set email alerts
|

Does the Arthroscopic Latarjet Procedure Effectively Correct “Off-Track” Hill-Sachs Lesions?

Abstract: The Latarjet procedure provides an effective treatment for "off-track" engaging Hill-Sachs lesions, despite an evident glenoid remodeling process. At a mean of 23 months postoperatively, a mean persisting enlargement of the glenoid arc of 14% beyond native dimensions remained, avoiding a recurrent "off-track" lesion in 32% of patients, which would otherwise have occurred with complete remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 42 publications
0
9
2
Order By: Relevance
“…Latarjet surgery is able to convert many, but not all, preoperative OFF-HS, and there is a difference in the recurrence rate between the persistent OFF-HS group versus the converted ON-HS group. Our findings differ from the results of Plath et al, 18 who described arthroscopic Latarjet as an isolated procedure and were able to convert all preoperative OFF-HS lesions to ON-HS lesions in a study of 23 shoulders with preand postoperative CT scans and a mean final follow-up of 23 months. Plath et al 18 also evaluated the role of a potential postoperative remodeling process of the coracoid graft on the final GT and concluded that remodeling occurred in the first 6 postoperative months.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Latarjet surgery is able to convert many, but not all, preoperative OFF-HS, and there is a difference in the recurrence rate between the persistent OFF-HS group versus the converted ON-HS group. Our findings differ from the results of Plath et al, 18 who described arthroscopic Latarjet as an isolated procedure and were able to convert all preoperative OFF-HS lesions to ON-HS lesions in a study of 23 shoulders with preand postoperative CT scans and a mean final follow-up of 23 months. Plath et al 18 also evaluated the role of a potential postoperative remodeling process of the coracoid graft on the final GT and concluded that remodeling occurred in the first 6 postoperative months.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings differ from the results of Plath et al, 18 who described arthroscopic Latarjet as an isolated procedure and were able to convert all preoperative OFF-HS lesions to ON-HS lesions in a study of 23 shoulders with preand postoperative CT scans and a mean final follow-up of 23 months. Plath et al 18 also evaluated the role of a potential postoperative remodeling process of the coracoid graft on the final GT and concluded that remodeling occurred in the first 6 postoperative months. In our study, no osteolysis or remodeling was observed on follow-up CT scan at a minimum 12-months follow-up, supporting the validity of our conclusions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We did not perform any remplissage procedures in the presence of a concomitant Hill-Sachs lesion. Plath et al 25 demonstrated that the Latarjet procedure transformed “off-track” Hill-Sachs lesions into “on-track” Hill-Sachs lesions. Those authors showed that at a mean of 23 months postoperatively, a mean persisting enlargement of the glenoid arc of 14% beyond native dimensions remained, avoiding a recurrent off-track lesion in 32% of patients, which would otherwise have occurred with complete remodeling.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 10 , 15 , 19 , 25 While traditionally performed in open fashion, the Latarjet procedure is increasingly being performed arthroscopically, with limited albeit promising evidence. 7 , 11 , 20 , 29 , 36 …”
Section: Discussionmentioning
confidence: 99%